Notas sobre a produção têxtil brasileira no final do século XVIII: novas evidências de Minas Gerais - Libby, Douglas Cole (Estudos Econômicos (São Paulo), 1997)
Based on the analysis of an original source and a re-examination of foreign travellers’ accounts, it is argued that sufficient evidence exists to suggest that the cottage textile industry was much more widespread in colonial Brazil than has previously been thought.  The Inventário dos teares existentes na Capitania de Minas Gerais, elaborated in an attempt to enforce the infamous Alvará of 1785, presents detailed information about that industry which allows for comparisons with the early phases of so-called European textile proto-industrialization and demonstrates some of the complexities of the colonial economy geared to the domestic market.